Medication Safety in Practice: Why Individual Knowledge and Supervisory Roles Show Limited Impact in Inpatient Wards - Sudarwati, Tri; Sri Sundari (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Medication errors are a major and common threat to patient safety in hospitals and may lead to adverse clinical outcomes and poor-quality care. Executive nurses, who are responsible for providing primary care such as medication administration, and head nurses, serving as a nursing practice leader, are core?to reducing medication errors. The objective of this research is to examine the level of significance between practical nurses' knowledge and the head nurse’s role toward medication errors in?the inpatient ward at RSI Siti Aisyah Madiun. Methods: The researchers employed a cross-sectional study and quantitatively collected the data. The entire population was counted through census sampling, which involved 100 managerial nurses and eight head nurses. The data were gathered by means of standardized and validated questionnaires. Statistical analyses such as Spearman's correlation and multiple linear regression were used to assess the separate and joint impacts of executive nurses’ knowledge and head nurses' roles on medication error occurrence. Results: The results indicated that the occurrence of medication errors was not significantly influenced by the practical nurses' knowledge (p = 0.956). Moreover, the roles of head nurses could not be traced as factors affecting the rates of medication errors (p = 0.893). The combined effect of both variables, as analysed simultaneously, also revealed no significant association with medication errors (p = 0.989) as indicated by a coefficient of determination of only 0.2%. From these results, it can be concluded that the roles of head nurses and adequate knowledge of practical nurses are, by themselves, not sufficient to significantly decrease the occurrence of medication errors. Conclusion: The absence of significant findings agrees with system-oriented patient safety theories, which argue that supervisory functions and an individual's knowledge cannot sufficiently prevent medication errors if there are no strong organizational and process, level safeguards. The study results point out the importance of system, based interventions. Examples of such interventions are building a positive patient safety culture, implementing risk management plans, standardizing medication procedures, and having non-punitive incident reporting procedures. Hence, the work for improving medication safety should be aimed at wide-ranging organizational and structural changes instead of merely individual qualifications.